Woven piezoelectric structure for stretchable energy harvester. Issue 1 (1st January 2013) - Yun, D.; Yun, K.‐S.
Abstract : The energy harvester is an attractive power source for wireless portable electronics, especially in applications for handheld and wearable electronic devices. Proposed is a woven piezoelectric structure for possible application as a wearable energy harvester. The proposed device consists of polymer column threads and a piezoelectric film weaving them into stitches in the row. Polymer patches are alternately patterned on the upper and bottom sides of the piezoelectric film, where the charges are generated when subjected to a stretching and contraction motion. A maximum peak power density of 0.63 mW/cm 2 was obtained from repeated stretching and contraction motion at an operation frequency of 8 Hz.